The Effect of Marketing Communication Strategies Through Celebgrams on Perceptions of the Product among Indonesian Millennials - Zein, Duddy; Wagiati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The rapid growth of social media has opened up vast opportunities for companies to capture the attention of potential customers. In this context, it has become imperative for brands to adapt their strategies to effectively target millennials through social media platforms. Notably, brands in the fashion industry have increasingly relied on online